S̄ạngkhmṣ̄ụks̄ʹā ṣ̄āl̊nālæaw̒tʹhnṭhrrm ḥạnm̂ṭhymkhụks̄ʹāpụ̄thụ̄ 3 - Sạ̀yxnạnt̒, S̄muthwṇis (H̄nạngs̄ụ̄xreīyn rāywisāphīnṭ̄hān, 2012)
Learning unit 1, Learn about North America and South America -- Learning unit 2, Learn how to live together -- Learning unit 3, Learning politics and government -- Learning unit 4, Interesting economics -- Learning unit 5, Sufficiently living -- Learning unit 6, Human development -- Learning unit 7, Studying the history of Rattanakosin period -- Learning unit 8, Wisdom and important people during the Rattanakosin period